Penilaian Kesehatan Koperasi Jasa Keuangan Syariah (KJKS) Berkah Madani Periode 2015-2016 - Fida Arumingtyas (University of Darussalam Gontor, 2017)
The analysis conducted will interpret ratios or financial data and its implications. This research is compiled to analyze health assessment KJKS Berkah Madani years 2015-2016 using a standard assessment of the Regulation of the Minister of State for Cooperatives and SMEs RI Number: 35.3/Per/M.KUKM/X/2007 on guidelines for a health assessment KJKS and UJKS Cooperative. The results of this study will be taken into consideration in the evaluation and a policy for KJKS Berkah Madani to improve their business performance so that stability is maintained and is expected to enhance public trust in this Islamic Microfinance Institutions. The approach used in this study is a quantitative and descriptive variables used are capital; asset quality; management; efficiency; and liquidity. Based on analysis of the health assessment KJKS Berkah Madani can be seen that score recapitulation of five variables in 2015 amounted to 73, 7832 and in 2016 increased to 79,9832 with the category Fairly Healthy.